DAMPAK BUDAYA POPULER BAGI MARU-MARU - Fabiola S Seite (TANGKOLEH PUTAI, 2019)
Current technological developments have diluted regional boundaries including clear boundaries about culture. The mass culture initiated by certain people is considered an absolute culture whose presence has increasingly eroded local culture including the Maru-maru dance. The Maru-maru dance in the Land of Lumahlatal is slowly being eroded due to the misunderstanding of the younger generation and the lack of inheritance processes being carried out. The results show that the younger generation is more interested in popular culture than local culture which is considered to have a barrier in terms of the language used when performing this dance.